ABLEISM KITSCH: THE AESTHETICS OF DISABILITY-RELATED ETHICS - Gruson-Wood, Julia Frances (Critical Disability Discourses, 2009)
This paper discusses the socio-political and ethical meanings of the various relationships between disablement, ableism, and ethics as they are generated through aesthetics, and does so by critiquing Tobin Siebers’s article “Disability Aesthetics” (2006). Siebers claims that disability has a tacit and valuable presence in western art. Disability is esteemed when represented in art, yet devalued in normative social relations. The author thus critiques disability aesthetics by investigating the beautiful, the sublime, “madness”, “mental impairment”, ableism, kitsch, and cultural appropriation. From this the author argues that disability aesthetics is a spectacularized, once removed, representational deviance from the humdrum normalization of western culture, providing contact with the intense, unusual, and shocking. By providing the gestures of transformation within the safety net of image, art is a virtual escape from the hyper-real predictability of hegemony; it is a secure place to experience, respond, flirt, and abandon difference in the vortex of representation.